2022
DOI: 10.3389/fmicb.2022.972294
|View full text |Cite
|
Sign up to set email alerts
|

The novel distribution of intracellular and extracellular flavonoids produced by Aspergillus sp. Gbtc 2, an endophytic fungus from Ginkgo biloba root

Abstract: Here, we reported a Ginkgo endophyte, Aspergillus sp. Gbtc 2, isolated from the root tissue. Its flavonoid biosynthesis pathway was reconstructed, the effect of phenylalanine on the production of flavonoids was explored, and the flavonoid metabolites were identified with the high-resolution Liquid chromatography–mass spectrometry (LC–MS). Some essential genes were annotated to form the upstream of the complete biosynthesis pathway, indicating that Aspergillus sp. Gbtc 2 has the ability to synthesize the C6–C3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…For example, Gymnopus and Sordariomycetes_unclassified in rhizosphere soil were positively correlated, while Plectosphaerella, Fusarium, and Gibberella were negatively correlated with flavonoids (Figure 8). Similar results were found in other medicinal plants, such as Cynomorium songaricum (Cui et al, 2018), R. palmatum (Chen et al, 2021), Ginkgo biloba (Wu et al, 2022), Polygonum hydropiper, and P. lapathifolium (Zhang et al, 2022). Furthermore, the correlation between secondary metabolites of F. dibotrys and endophytic fungi in the rhizome and rhizosphere soil fungi was significantly different (Figures 7C, D), which revealed that endophytic fungi and rhizosphere soil fungi could interact with secondary metabolites in a different manner.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Gymnopus and Sordariomycetes_unclassified in rhizosphere soil were positively correlated, while Plectosphaerella, Fusarium, and Gibberella were negatively correlated with flavonoids (Figure 8). Similar results were found in other medicinal plants, such as Cynomorium songaricum (Cui et al, 2018), R. palmatum (Chen et al, 2021), Ginkgo biloba (Wu et al, 2022), Polygonum hydropiper, and P. lapathifolium (Zhang et al, 2022). Furthermore, the correlation between secondary metabolites of F. dibotrys and endophytic fungi in the rhizome and rhizosphere soil fungi was significantly different (Figures 7C, D), which revealed that endophytic fungi and rhizosphere soil fungi could interact with secondary metabolites in a different manner.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the C-C is located at 1030.65 cm −1 . The presence of flavonoids and phenolic acids in the tested extract can be fundamentally linked to the occurrence of absorption bands related to C=C, C=O, C-O, C-N, OH, and CH ( Wu et al, 2022 ). These functional groups contribute to the stability of the prepared ZnONPs as well as the reduction of Zn metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…SA17. (Wu et al, 2022). These functional groups contribute to the stability of the prepared ZnONPs as well as the reduction of Zn metal ions.…”
Section: Fourier Transforms Infrared Spectroscopy Analysismentioning
confidence: 99%
“…Since the discovery of the taxol-producing endophytic fungus Taxomyces andreanae [47], the bioactive compounds derived from fungal endophytes have attracted pharmacological research attention. Our lab has successfully isolated fungal endophytes from a variety of naturally occurring medicinal plants, such as Ginkgo biloba L. [48], with the The enzymes found in the genome sequences of the strain based on KEGG annotation are presented in red; the sanguinarine and chelerythrine biosynthesis enzymes queried against the strain's genome are in pink; and the not-found and unstudied enzymes are in green and black, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the taxol-producing endophytic fungus Taxomyces andreanae [ 47 ], the bioactive compounds derived from fungal endophytes have attracted pharmacological research attention. Our lab has successfully isolated fungal endophytes from a variety of naturally occurring medicinal plants, such as Ginkgo biloba L. [ 48 ], with the capability of producing plant natural products comparable to their host plants. Employing endophytic fungi fermentation to produce natural bioactive compounds is an effective and reliable strategy when proper technological advancement is used in mediating the capability of these entities.…”
Section: Discussionmentioning
confidence: 99%